Model Predictive Control of Shunt Active Filter for Power Quality Improvement in Distribution systems - Kumaresan, S; Sait, H. Habeebullah (International Journal of Computer Sciences and Engineering, 2018)
The presence of nonlinear loads in the distribution system results in poor power quality parameters such as low total harmonic distortion (THD), poor distortion power factor and produces nearby communication interference. Shunt active power filters (SAF) are used for improving the power quality in high power distribution systems. The Shunt active filter controller has the low frequency voltage control loop for regulating the DC voltage of SAF capacitor and the faster acting current control loop for realizing the compensation current. Conventionally, the current and voltage controllers are realized by distinct hysteresis and PI controllers respectively. This paper discusses the finite control set Model Predictive Control (FCS- MPC) that realizes the voltage and current control of SAF. The reference current of SAF is calculated from the instantaneous PQ theory. The phase locked loop (PLL) is adopted for generating the reference value of compensation currents. A discrete time mathematical model of the SAF is presented and the design steps of FCS- MPC are explained. The control objectives such as compensation current error minimization and DC link voltage regulation are defined in cost functions. During each sampling interval, the controlled variables such as SAF current and DC voltage of the capacitor are predicted by the mathematical model. The predicted variables are assessed by the cost function minimization and the switching state that provides minimum cost function is selected and applied to the SAF. The performance of the FCS-MPC strategy for the current control of SAF is validated for sinusoidal and non-sinusoidal distribution system voltages in MATLAB-SIMULINK simulations.